Awareness and Stimulus-Driven Spatial Attention as Independent Processes - Baier, Diane; Goller, Florian; Ansorge, Ulrich (Frontiers in Human Neuroscience, 2020)
To investigate the relation between attention and awareness, we manipulated visibility/awareness and stimulus-driven attention capture among metacontrast-masked visual stimuli. By varying the time interval between target and mask, we manipulated target visibility measured as target discrimination accuracies (ACCs; Experiments 1 and 2) and as subjective awareness ratings (Experiment 3). To modulate stimulus-driven attention capture, we presented the masked target either as a color-singleton (the target stands out by its unique color among homogeneously colored non-singletons), as a non-singleton together with a distractor singleton elsewhere (an irrelevant distractor has a unique color, while the target is colored like the other stimuli), or without a singleton (no stimulus stands out; only in Experiment 1). As color singletons capture attention in a stimulus-driven way, we expected target visibility/discrimination performance to be best for target singletons and worst with distractor singletons. In Experiments 1 and 2, we confirmed that the masking interval and the singleton manipulation influenced ACCs in an independent way, and that attention capture by the singletons, with facilitated performance in target-singleton compared to distractor-singleton conditions, was found regardless of the interval-induced (in-) visibility of the targets. In Experiment 1, we also confirmed that attention capture was the same among participants with worse and better visibility/discrimination performance. In Experiment 2, we confirmed attention capture by color singletons with better discrimination performance for probes presented at singleton position, compared to other positions. Finally, in Experiment 3, we found that attention capture by target singletons also increased target awareness and that this capture effect on subjective awareness was independent of the effect of the masking interval, too. Together, results provide new evidence that stimulus-driven attention and awareness operate independently from one another and that stimulus-driven attention capture can precede awareness.